Culinary and creative writing: when two worlds collide / Muhammad Amirul Azeem Azmi and Suhaili Mohd Yusof - Azmi, Muhammad Amirul Azeem; Mohd Yusof, Suhaili (Academy of Language Studies, 2023)
Creative writing is usually associated with written works such as short stories or poems while a recipe is considered to be a form of technical writing due to the precise measurements of the ingredients. Creative writing is currently gaining popularity among the younger generation, but cookbooks are deemed irrelevant as recipes can be found online on blogs and social media platforms. However, beyond recipe compilation, a cookbook can also be used as a heritage preservation tool. Thus, it is important to get the younger generation interested in reading and owning cookbooks. To do so, cookbook authors should explore new ways of presenting the recipes to their readers. Therefore, the objectives of this project are to promote the usefulness of creative writing skills and to innovate the typical writing style of a cookbook by using creative writing elements. In this book, selected family recipes are rewritten as poems and short stories, which are then compiled as an e-book. Positive response from the participants of the survey indicates that there is a market for this innovative product.